A CONTRIBUTION TO THE CRANIOLOGY OF MODERN AND SUBFOSSIL WOLVES IN ARMENIA - Manaseran, Nina; Kasaban, Mamikon; Balan, Luba; Barsegan, Nelli; Bagoan, Asmik; Gendzan, Andranik (History, Archeology and Ethnography of the Caucasus, 2026)
This article presents the first craniometric study of seven wolves sacrificed and buried at an Early Bronze Age sanctuary (28th–26th centuries BCE) in the Mets Sepasar settlement. The study identifies specific craniometric parameters and analyzes morphometric skull variability across a chronological range from the Early Bronze Age to the present day. Comparative analyses were conducted using skull parameters of subfossil dogs and modern wolves from Armenia, sourced from the collections of the Scientific Center of Zoology and Hydroecology of the National Academy of Sciences of the Republic of Armenia. The research establishes ranges of individual variation and highlights differences in cranial size and structure between subfossil and modern representatives of the genus Canis. The wolf skulls from the Mets Sepasar archaeological site represent unique Early Bronze Age material, as they constitute a unique dataset that reflect various aspects of ecology and ritual practices of the time. The results demonstrate similarities in the absolute parameters of subfossil and modern wolves; notably, the subfossil wolves from the Mets Sepasar sanctuary exhibit larger dimensions compared to modern wolves from other regions of Armenia. Furthermore, subfossil dogs were found to be clearly distinct from both modern and subfossil wolves across all measured parameters. These findings enrich the craniological data for the genus Canis, providing valuable comparative material for identifying bone remains in future craniological and zoological research. Such data significantly expands our understanding of the cultural and ecological dimensions of human-wildlife interaction in the past. These results serve as a critical tool for identifying skeletal remains in archaeological excavations and contribute to the reconstruction of Ancient Armenian ecosystems.
Keywords: subfossil wolf; subfossil dog; Bronze Age; craniometry; wolf burials; Mets Sepasar